Feminists, feminisms, and advertising : some restrictions apply - Golombisky, Kim; Kreshel, Peggy J. (Peggy Jean), 1953- (Lexington Books, 2017)
This book is the first to offer explicitly feminist views on the shared histories of the advertising industry and women's movement. Contributors consider the ways advertisers encode race, ethnicity, gender, and heteronormativity into advertising practices and messages, as well as the ways intersectional audiences and consumers resist.